RR interval variations in young male diabetics. - Murray, A (1975)
The beat-to-beat (RR interval) variation in resting heart rate was used to detect possible autonomic nerve damage in a group of 42 young asymptomatic male diabetics, employing a sensitive electrocardiographic computer technique. Compared with 25 age-matched controls, the diabetics showed both a significantly smaller mean RR interval (P less than 0.005) and less RR interval variation (P less than 0.001). Whereas only 4 of the diabetic subjects had shorter mean RR intervals, 22 (52%) of the diabetics had RR interval variations that were less than any of the normal subjects. This reduction in heart rate variation has not been previously reported in diabetics without clinical features of autonomic neuropathy and might provide a sensitive method of assessing early autonomic nerve involvement in diabetes.